Translanguaging Practices in Secondary Level English Classrooms in Indigenous Communities of Bangladesh - Amin, Naiem Al (English Language Teaching Perspectives, 2025)
This research investigates translanguaging practices in secondary-level English classrooms in Indigenous communities in Bangladesh, where English proficiency is crucial for academic and career success, particularly for ethnic minorities. Traditional monolingual teaching methods often fail to address the linguistic diversity in these settings, limiting students’ language acquisition. The study explores teachers’ awareness and perspectives on translanguaging and how much they incorporate it into their teaching. Data was collected through focus group discussions with students, interviews with teachers, and classroom observations. This study reveals that many teachers are unfamiliar with translanguaging, and existing policies favoring Bangla and English restrict the use of native languages in classrooms. While few teachers support translanguaging for promoting inclusivity, most of the teachers express concerns that it may impede students’ English language development. It has been found that students benefit from using their native languages, particularly during group work, although many teachers discourage this practice. Key barriers were insufficient teacher training, unfamiliarity with native languages, and institutional resistance. Nevertheless, translanguaging is used to enhance student engagement and comprehension. This research highlights the need for educational reforms that embrace linguistic diversity, advocating for policy changes to create inclusive classrooms and improve education for ethnic minority students in Bangladesh.